Digital Agility in the Organization as a Response to Technological Changes: Analysis of the IT Sector in Croatia (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Digital agility is the answer to understanding and adapting to technological changes in business. Organizations continuously adapt to changes and the successful degree of adaptation to applications is decided for potential prosperity or the very resilience of business. The advantages that bring successful implementation in the form of digital agility through effective digital communication will be reflected in time management, processes will be accelerated and communication will be actively managed for quality. Open change organizations will shape their employees' attitudes towards digital processes and tools. Agile organizations are based on values ​​and principles, which is achieved by taking active roles during working hours and through productive communication. The goal of this paper is to analyze digital agility through the dynamics of communication in IT sector organizations, which by their nature should be the bearer of technological changes. The methodology used in the research is the degree of contact with the business entity in the form of digital communication via e-mail, where the time period of receiving feedback is measured. The scientific contribution of this research is the analysis of the IT sector in Croatia as a strategic leader of change and investment in innovation and defining the development directions of the economy.